Relationship between the quantity of B (a) P and mutagenicity in a small diesel engine exhaust particles under different loads - NADAHARA, Soichi; KIKUCHI, Tadashi; FURUYA, Keiichi; KINOUCHI, Takemi; OHNISHI, Yoshinari; WAKISAKA, Kazumi (Journal of Japan Society of Air Pollution, 1982)
The relationship between diesel engine operating conditions and a quantity of emitted benzo (a) pyrene in diesel particulate matter produced under the incomplete combustion was examined in comparison with mutagenic assays. Throughout this study, YANMAR NSA 40C diesel engine (4-stroke, single-cylinder, displacement; 269 cc) was utilized. The engine was operated under a constant revolution (2000 rpm) with a variety of loads (0, 250, 500, 750, 1000 watt) and was loaded by a connction of a electric resistance with a generator. Particulate sample were collected on a glass fiber filter (20.3×25.4 cm) using a collection apparatus, in which total exhaust gas introduced diluting with prefiltered air. The filters containing the particulates were Soxhlet-extracted with benzene (100 ml) for 8 h, concentrated to 10 ml. The extracted benzo (a) pyrene was quantitated by using a high performance liquid chromatography equipped with fluorescence detector. Mutagenic assays of the extracts of the exhaust particulates were carried out by the procedure of Ames et al. Throughout the previous experimental runs, fuel consumptiom, exhaust gas volume, particulate quantity in the exhaust, quantity of benzo (a) pyrene and mutagenic activity toward load were examined. A certain correlation was observed between the quantity of benzo (a) pyrene and the mutagenic activity had the minimum values at 500, 750 watt, respectively. Mutagenicity might correlate to the quantity of benzo (a) pyrene in the range of below 500 watt and increase in the range above 500 watt because of increase of mutagens other than benzo (a) pyrene.